Propofol Inhibits Androgen Production in Rat Immature Leydig Cells - Wang, Yiyan; Ge, Fei; Li, Xiaoheng; Ni, Chaobo; Wu, Keyang; Zheng, Wenwen; Chen, Yong; Lian, Qingquan; Ge, Ren-Shan (Frontiers in Pharmacology, 2019)
Background: Propofol is a widely used anesthetic. Whether propofol inhibits androgen production in rat Leydig cells and the underlying mechanism is unclear. The objective of this study as to examine effects of propofol on rat primary immature Leydig cells and to define propofol-induced inhibition of steroidogenic enzymes in both rat and human testes in vitro. Methods: Immature Leydig cells were purified from 35-day-old male Sprague Dawley rats and were exposed to propofol for 3 h. The androgen production of Leydig cells under basal, luteinizing hormone, 8bromo-cAMP, and steroid-substrate stimulated conditions and gene expression of Leydig cells after exposure to propofol were measured. Immature Leydig cells were treated with propofol for 3 h and switched to propofol-free medium for additional 3 and 9 h to test whether the drug is reversible. 3H-Steroids were used to evaluate the direct action of propofol on cholesterol side chain cleavage (CYP11A1), 3b-hydroxysteroid dehydrogenase (HSD3B), 17a-hydroxylase/17, 20-lyase (CYP17A1), and 17b-hydroxysteroid dehydrogenase 3 (HSD17B3) activities in rat and human testes in vitro. Results: Propofol significantly lowered luteinizing hormone and 8bromo-cAMP stimulated androgen production after 3-h culture. Further investigation showed that propofol down-regulated Cyp11a1 and Cyp17a1 and their protein expression at 5 and 50 uM although it up-regulated Lhcgr expression at 50 uM. Propofol significantly suppressed phosphorylation of ERK1/2 and induced ROS production in immature Leydig cells at 5 and 50 uM. Propofol significantly induced apoptosis of immature Leydig cells at 50 uM. Propofol specifically inhibited rat and human testis HSD3B activities in vitro. The half maximal inhibitory concentration values of propofol for rat and human HSD3B enzymes were 1.011 ± 0.065 and 3.498 ± 0.067 uM, respectively. The mode of action of propofol on HSD3B was competitive when pregnenolone was added. At 50 µM, propofol did not directly inhibit rat and human testis CYP11A1, CYP17A1, and HSD17B3 activities in vitro. Conclusion: Propofol inhibits androgen production via both directly inhibiting HSD3B activity and down-regulating Cyp11a1 and Cyp17a1 expression in Leydig cells. Suppression of steroidogenic enzymes is presumably associated with the lower production of androgen in Leydig cells after propofol treatment. However, propofol-induced inhibition on androgen production is reversible.